The conveyor belt longitudinal tear on-line detection based on improved SSR algorithm - Li, Jie; Miao, Changyun (Optik (Stuttgart), 2016)
The longitudinal tear failure of conveyor belt is one of the important reasons which leads to major security incidents, such as, production halts, transporting materials losses, equipment damage and some casualties, etc. An on-line detection method on longitudinal tear failure of conveyor belt images based on improved SSR Algorithm is proposed in this paper. First, the appropriate scale parameter is selected, and the images which line-scan digital camera collected are processed by the improved SSR algorithm, then to extract the conveyor belt longitudinal tear characteristics information, including the area, slightness and rectangle degree, etc, thereby concluding whether there was a longitudinal tear failure on conveyor belt on the basis of the collected characteristics information. All the finished detections showed that this method could detect the longitudinal tear failure of conveyor belt images with higher accuracy and faster processing speed, meanwhile, the online detection on longitudinal tear failure of conveyor belt images can be achieved.